2012
DOI: 10.1007/s00425-012-1795-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of drought on the microtranscriptome of field-grown sugarcane plants

Abstract: Sugarcane (Saccharum spp.) is the most promising crop for renewable energy. Among the diverse stresses that affect plant productivity, drought stress frequently causes losses in sugarcane fields. Although several studies have addressed plant responses to drought using controlled environments, plant responses under field conditions are largely unknown. Recently, microRNA (miRNA)-mediated post-transcriptional regulation has been described as an important and decisive component in vegetal development and stress r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 82 publications
3
39
0
3
Order By: Relevance
“…Upregulation of miR394 in J. pentantha is comparable to those reported in cotton (0.87 fold increase) exposed to drought stress (Xie et al 2014). In another study, miR394 was shown to be downregulated in high-tolerant sugarcane cultivar but upregulated in the sensitive cultivars (Gentile et al 2013). In these cultivars, (Liu et al 2007;Ballen-Taborda et al 2013;Turner et al 2013).…”
Section: Resultssupporting
confidence: 70%
“…Upregulation of miR394 in J. pentantha is comparable to those reported in cotton (0.87 fold increase) exposed to drought stress (Xie et al 2014). In another study, miR394 was shown to be downregulated in high-tolerant sugarcane cultivar but upregulated in the sensitive cultivars (Gentile et al 2013). In these cultivars, (Liu et al 2007;Ballen-Taborda et al 2013;Turner et al 2013).…”
Section: Resultssupporting
confidence: 70%
“…Sequencing profiles revealed that most miRNA families responded similarly to both the stressors (drought or heat) while a fewmiRNA families showed stress-specific response, i.e., induced or repressed only under drought or heat in switchgrass ( Table 2). The altered expression of several miRNAs following drought or heat in this study was largely in agreement with several earlier reports that studied miRNA responses to stress conditions ingrasses[40,41, [53][54][55][56][57][58][59][60][61][62][63][64][65][66].Nevertheless, there are alsoinstances in which our study did not correspond with some of the earlier reports. For instance,drought stress repressed the expression of miR166 in wheat [53], rice [57] and sugarcane [63] while we found it is induced in switchgrass.Drought downregulated the expression of miR167 and miR168 in switchgrass [40] andmiR168 in rice [57]butthese miRNAs are found to be up-regulated by drought in this study.The miR396 levels were repressed in wheat [53],rice [57] and sugarcane [63]under drought but it is up regulated under drought in the present study.…”
Section: Discussionsupporting
confidence: 73%
“…Deep sequencing has been applied to identify sugarcane miRNAs in roots subjected to drought stress, plantlets subjected to salt stress and plantlets subjected to pathogen infection (Thiebaut et al 2012). miRNA species associated with water deficit in leaves of 3-month-old glasshouse grown and 7-month-old field grown sugarcane plants have been identified (Bottino et al 2013;Ferreira et al 2012;Gentile et al 2013). Small RNAs associated with axillary bud outgrowth have also been analysed (Ortiz-Morea et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In combination, these enabling technologies and molecular tools have facilitated metabolic engineering of the sugar profile (Mudge et al 2013). Furthermore, investigations have begun into the small RNA (sRNA) component of the sugarcane transcriptome (Bottino et al 2013;Ferreira et al 2012;Gentile et al 2013;Zanca et al 2010).…”
Section: Introductionmentioning
confidence: 99%